Ultramicroscopic changes of rats parathyroid glands and thymus after single administration of cyclophosphamide at the different periiods of observation - Erokhina, Victoriia; Avilova, Olga (Wiadomosci Lekarskie, 2019)
Background. Cyclophosphamide has wide spectrum usage as first-line drug in cancer chemotherapy that is why a detailed study of its effect on individual cell populations is of great interest for science and practice. The interaction of the nervous, immune and endocrine systems plays essential role in the homeostasis maintaining. Objectives. This study aimed to investigate the ultramicroscopic changes that occur in the parathyroid glands and thymus of male rats after cyclophosphamide administration. Methods. Twenty-four WAG matured male rats were divided randomly into two groups. The first group served as control and was provided 0.9% soluble sodium chloride. The second group received cyclophosphamide in a dosage 200 mg/kg of body weight of animal by intramuscular single injection. All animals were sacrificed on the 7th and 30th day after injection. Parathyroid gland and thymus specimens were dissected out and processed for electron microscopy. Results. The results showed that cyclophosphamide exposure caused marked ultramicroscopic changes in rats parathyroid glands and thymus. On the 7th day after immunosuppression, the nuclei of parathyrocytes have deep wavy invaginations, amount of the organelles that participate in the protein synthesis is reduced to a minimum in the cytoplasm of the chief cells. Characteristic feature is the appearance of numerous plasma cells and active macrophages in thymus. There is a tendency to normalization of the parathyroid structure on the 30th day after administration of cyclophosphamide and reduction of mitotic activity of lymphocytes in thymus, which points to the development of involution process. Conclusion. This data can be successfully extrapolated from experimental animals to humans.
Keywords: immunosuppression; parathyroid glands; thymus; immunosuppression; cyclophosphamide